AUDITORIA FINANCIERA A LA COMPAÑÍA TRANSPORTE REINA DE LORETO KING LORETO S.A., UBICADA EN LA CIUDAD DE LORETO PROVINCIA DE ORELLANA DEL PERIODO 2015 - Gutiérrez Puraquilla, Carmela Carola (2018)
The present investigation was carried out in order to meet one of the prerequisites for the degree in Accounting and Auditing. CPA., And that the results obtained in this work, serve as a fundamental contribution in the improvement of the Transport Company, because it has seen the need to know the financial situation in which the aforementioned company is already located, with this investigation aims to help it manage its revenues and expenses in a better way so that the company makes better decisions always thinking about the growth of it. With the completion of the Financial Audit, the proposed objectives are met through the application of techniques and procedures to determine the reasonableness of the presented balances, which allowed analyzing the legality, veracity and ownership of the documentation that supported the financial operations of the institution to finally issue the audit report where the comments, conclusions and recommendations for the appropriate decision making were presented. Once the entire process applied in the Company was concluded, it was concluded that the Financial Audit has become an indispensable system for evaluating the development of economic activities in order to observe findings that may jeopardize the proper functioning of the entity. what is recommended to the management to apply this type of work in a frequent way to safeguard the resources of the entity.